Analysis of the Influence of Fiqh and Maqasid al-Syariah in the Formation of Islamic Legal Policy in Indonesia - Mokodenseho, Sabil; Siregar, Retnawati; Muslim, Shohib; Hasibuan, Kalijunjung; Rahman, Rahman (West Science Islamic Studies, 2024)
This research delves into the complex interplay of Fiqh and Maqasid al-Syariah in shaping Islamic legal policy in Indonesia, employing qualitative methods such as in-depth interviews, content analysis, and document analysis. The study reveals the explicit incorporation of Fiqh in legislation and its influence on judicial decisions, highlighting the enduring role of traditional Islamic jurisprudence. Simultaneously, Maqasid al-Syariah emerges as a guiding ethical framework, fostering adaptability and providing opportunities for aligning legal objectives with overarching Islamic principles. The research explores the harmonization efforts, tensions, and collaborative initiatives in navigating the intersection between Fiqh, Maqasid al-Syariah, and contemporary legal frameworks. The findings contribute to a nuanced understanding of the dynamic relationship between tradition and adaptation in Islamic legal policymaking in Indonesia